Rebuilding knowledge: Opportunities and risks for higher education in post-conflict regions - Hart Nadav Feuer; Anna-Katharina Hornidge; Conrad Schetter (University of Bonn, Center for Development Research (ZEF), 2013)
The transition from violence and instability to peace and prosperity is rarely linear, but rather defined more by its complexity and the alignment of often-surprising conditions. The rebuilding and reorganization of the higher education sector, in particular, is increasingly being recognized as both a driver and a consequence of this complex transition, which is marked by a sustained process of negotiation between various local factions and with external actors. In so-called 'intervention societies' where humanitarian relief and long-term development intersect, re-envisioning what types of 'knowledge' to promote through higher education is very much at the heart of re-writing the social contract and investing in peace and productivity. Indeed, in development circles, the reform or reconstruction of systems of higher education is now viewed as an opportunity to achieve the longterm goals of integration, intercultural communication, and tolerance building. As an outlet for young people (many of which are demobilized soldiers) and a space for breaking down knowledge monopolies in society, universities are emblematic of the aspirations for training a post-conflict generation of civil servants, politicians and thinkers, as well as for interfacing with the outside world. Keeping the unique characteristics and timeline of each conflict in mind, this paper investigates, on the one hand, comparable trends in macro-level discourse and programming around post-conflict higher education in different countries and, on the other hand, evaluates on the very routine and practical level, the challenges faced by students, teachers, and administrators to conceive of, regulate and re-build systems of higher education and the corresponding academic social life on campuses. In this, we look at how the passive byproducts of knowledge creation in a university atmosphere, such as gaining academic reflexivity, socializing with former enemies, and reproducing societal hierarchies is intertwined with content and learning.
Keywords: 330; post-conflict; higher education; knowledge; rebuilding; peacebuilding